2021
DOI: 10.21123/bsj.2021.18.4(suppl.).1545
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing, Structuring, and Characterizing Bioactivities of .Cr(III), La(III), and Ce(III) .Complexes with Nitrogen, Oxygen .and Sulpher donor bidentate Schiff base ligands

Abstract: Two Schiff bases, namely, 3-(benzylidene amino) -2-thioxo-6-methyl 2,5-dihydropyrimidine-4(3H)-one (LS])and 3-(benzylidene amino)-6-methyl pyrimidine 4(3H, 5H)-dione(LA)as chelating ligands), were used to prepare some complexes of Cr(III), La(III), and Ce(III)] ions. Standard physico-chemical procedures including metal analysis M%, element microanalysis (C.H.N.S) , magnetic susceptibility, conductometric measurements, FT-IR and UV-visible Spectra were used to identify Metal (III) complexes and  Schiff bases (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…When compared to the ligand spectrum, all complex spectra show the elimination of the (O -H) phenolic and the shifted azo group (N=N). This demonstrates that the ligand and metal ion were coordinated via the nitrogen and oxygen atoms as well as via the nitrogen of the azo group 28 . In addition, new bands have been observed that belong to (M-N) at (593, 585, 562, and 554) cm -1 for the complexes of Ni, Pd, Pt, and Au, respectively, and (M-O) at (514, 521, 527, and 489) cm -1 for the complexes Ni, Pd, Pt, and Au, respectively, supporting the occurrence of coordination through the nitrogen and oxygen atoms [29][30][31] ,Ni(II) complex as shown in Fig 9 . Every complex's new bands were discovered to correlate with its coordinated water molecules 32 .…”
Section: Infrared Spectramentioning
confidence: 91%
“…When compared to the ligand spectrum, all complex spectra show the elimination of the (O -H) phenolic and the shifted azo group (N=N). This demonstrates that the ligand and metal ion were coordinated via the nitrogen and oxygen atoms as well as via the nitrogen of the azo group 28 . In addition, new bands have been observed that belong to (M-N) at (593, 585, 562, and 554) cm -1 for the complexes of Ni, Pd, Pt, and Au, respectively, and (M-O) at (514, 521, 527, and 489) cm -1 for the complexes Ni, Pd, Pt, and Au, respectively, supporting the occurrence of coordination through the nitrogen and oxygen atoms [29][30][31] ,Ni(II) complex as shown in Fig 9 . Every complex's new bands were discovered to correlate with its coordinated water molecules 32 .…”
Section: Infrared Spectramentioning
confidence: 91%
“…Table 5 shows the antimicrobial activities of the (1B-3C) compounds. The DMSO was used as a control substance 37 .…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…5. NIST XCOM software has been used to estimate the theoretical values of mass attenuation coefficient [13][14][15][16][17][18][19][20] . The mass attenuation coefficient is a crucial parameter in the field of gamma ray shielding materials [21][22][23] .…”
Section: Figure 4 Density and Molar Volume Vs Mole Fraction Of Lead O...mentioning
confidence: 99%